1983
DOI: 10.1073/pnas.80.10.3101
|View full text |Cite
|
Sign up to set email alerts
|

Microheterogeneity ("neurotypy") of neurofilament proteins.

Abstract: Neurofilaments purified from adult rat brainstem by two methods were electrophoresed on NaDodSO4/polyacrylamide gels to separate the triplet proteins (approximate Mrs of 200,000, 155,000, and 68,000) which, in turn, were electroblotted onto nitrocellulose paper. On Coomassie blue-stained gels that were not electroblotted, the same banding pattern was seen with both methods of preparation. Immunocytochemical staining of the electroblots with each of five monoclonal antibodies revealed that three of the monoclon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
48
0
1

Year Published

1983
1983
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(51 citation statements)
references
References 38 publications
2
48
0
1
Order By: Relevance
“…Thus, all structures stained by antibodies of the anti-neurofibrillar group were not stained by antibodies from the anti-perikaryonal-neurofibrillar group, or vice versa. Nevertheless, analysis of electroblots of brain homogenates, cytoskeletal preparations (3,4), and isolated neurofilaments (5) showed that antibodies of both groups reacted exclusively with doublet Mr 200,000 bands and one Mr 150,000 band of the Mr neurofilament triplet (three major polypeptides of Mrs 200,000, 150,000, and 68,000) (6). These data and differences in immunocytochemical reaction of each antibody in each group suggested two levels of heterogeneity of neurofilaments, one detectable by difference of reaction between the anti-neurofibrillar and anti-perikaryonal-neurofibrillar group and the other by differences with antibodies within each of these groups.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, all structures stained by antibodies of the anti-neurofibrillar group were not stained by antibodies from the anti-perikaryonal-neurofibrillar group, or vice versa. Nevertheless, analysis of electroblots of brain homogenates, cytoskeletal preparations (3,4), and isolated neurofilaments (5) showed that antibodies of both groups reacted exclusively with doublet Mr 200,000 bands and one Mr 150,000 band of the Mr neurofilament triplet (three major polypeptides of Mrs 200,000, 150,000, and 68,000) (6). These data and differences in immunocytochemical reaction of each antibody in each group suggested two levels of heterogeneity of neurofilaments, one detectable by difference of reaction between the anti-neurofibrillar and anti-perikaryonal-neurofibrillar group and the other by differences with antibodies within each of these groups.…”
mentioning
confidence: 99%
“…The incubated electroblots and the paraffin sections were stained immunocytochemically (9, 10) with mouse peroxidaseanti-peroxidase prepared from monoclonal anti-peroxidase (Clono PAP) (2,6,11) tibodies 06-17, 04-7, and 07-5 (Fig. 2).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This may imply that the 2 bat species may not be as phylogenetically close as we presume. It could also be that the EC is a less adept model for this hypothesis, and a lack of immunoreactivity in the EC of Strawcoloured fruit bat, may indicate that the function subserved by SMI-32 immunoreactive cytoskeletal components may either not be required or is assumed by another protein (Campbell and Morrison 1989;Goldstein et al 1983). There are similar reports of a lack of SMI-32 immunoreactivity in the EC that include an Australian echidna (Tachyglossus aculeatus) and the Tamar wallaby (Macropus eugenii) Hassiotis et al 2004;Hassiotis et al 2005).…”
Section: Chemoarchitectonic Comparisonmentioning
confidence: 99%
“…Proteins separated in two-dimensional gels were blotted onto a nitrocellulose paper and allowed to react with the anti-220 K antibody. Bound antibody was stained with the peroxidase-antiperoxidase system (2,14). 170 K and 220 K components (Fig.…”
mentioning
confidence: 99%